EVALUATION OF INSTITUTIONAL CHANGE IN TOUR AGENTS BRANCH - NEW INSTITUTIONAL ECONOMICS ANALYTICAL FRAMEWORK - Minko GEORGIEV; Boryana IVANOVA; Ivanka DIMITROVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study aims to adapt an analytical framework for the analysis of the institutional environment and institutional change. The activity of the tour agents (TA), part of the tourism sector of Bulgaria in the period 2005 - 202 , was a subject of the study. The institutional impact is integrated with the transaction cost economics, monitoring the dynamics of rules and distribution of economic effects. Relative institutional analysis retrospectively follows the rules. Legal realism explains the institutions and measures used to resolve concomitant crises (Covid- 9), turning them into synthetic values. Discrete structural analysis fragments processes and thus makes coordination clear. The adaptation of the actors is analysed by transaction cost (TC) measurement. The results show that the institutional changes are many and are designed in favour of the great actors. TC are increasing, and TA problems are systemic and are not a consequence of concomitant crises.